Preparation method and application of In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution

Through the preparation of In2O3/ZnCdS/Pt composite materials, a heterostructure is formed using MIL-68 (In) conversion and femtosecond laser etching technology, which solves the problems of low carrier separation efficiency and short life of ZnCdS photocatalyst, and realizes the High-efficiency photocatalytic hydrogen evolution and anti-photocorrosion effects.

CN119215993APending Publication Date: 2024-12-31NORTH CHINA UNIV OF WATER RESOURCES & ELECTRIC POWER
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411281385.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing ZnCdS photocatalysts have problems with low carrier separation efficiency, short lifetime and easy photocorrosion, and traditional cocatalysts such as NiO have limited performance improvement.

Method used

Using the preparation method of In2O3/ZnCdS/Pt composite material, In2O3 is obtained through MIL-68 (In) conversion, and a heterostructure is formed with ZnCdS. Pt is used as a cocatalyst and combined with ultrasonic dissolution, femtosecond laser etching and other technologies to form Highly efficient photocatalyst.

Benefits of technology

The efficiency and output rate of photocatalytic hydrogen evolution are significantly improved, the life of the material is extended, the photocorrosion phenomenon is reduced, and the photocatalytic activity is enhanced through multi-interface regulation and active sites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215993A_ABST
    Figure CN119215993A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano composite materials, in particular to a preparation method of an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution, which comprises the following steps: preparing hollow rod-shaped In2O3 by using MIL-68 as a precursor, and then loading ZnCdS nanoparticles and Pt clusters on the hollow rod-shaped In2O3 to successfully prepare the In2O3 / ZnCdS / Pt composite material. The prepared In2O3 / ZnCdS / Pt composite material is applied to photocatalytic hydrogen production; the In2O3 / ZnCdS / Pt composite material prepared by the preparation method disclosed by the invention shows excellent performance when being applied to photocatalytic hydrogen evolution. Wherein In2O3 and Pt are used as double promoters, so that the photocatalytic activity is efficiently improved, and the recombination of electron-hole pairs is inhibited by the construction of heterojunction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanocomposite materials, and in particular to a preparation method and application of an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution. Background Art

[0002] Photocatalytic hydrogen production is powered by solar energy and uses cheap and abundant water as raw material. It includes three key steps: absorption of sunlight, separation of photoelectron-hole pairs, and reduction of electrons and protons in water. Current research focuses on the synthesis of economical, stable and efficient photocatalysts. ZnCdS, as a ternary sulfide, has a suitable band gap, visible light response, and good photocatalytic activity, and has a good hydrogen production effect. However, pure ZnCdS has low separation efficiency of photoexcited carriers, short lifetime, and is easily corroded by light. Therefore, adding co-catalysts to ZnCdS and constructing heterostructures are effective strategies to solve the above problems.

[0003] As mentioned above, in order to solve the problems of low separation efficiency, short life and easy photocorrosion of ZnCdS, methods such as adding a co-catalyst and constructing a heterojunction can be used. Pt is an excellent co-catalyst, but it faces the problem of high price and is not easy to form a heterostructure with ZnCdS. Metal oxide-sulfide heterojunctions are easy to construct. For example, a patent application with application number CN202310661785.6 discloses a method for preparing a ZnCdS / NiO composite photocatalyst and its application, but the NiO co-catalyst has limited performance improvement.

[0004] In order to solve the above problems, the present invention designs a preparation method and application of an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a preparation method and application of an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution.

[0006] A method for preparing an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution comprises the following steps:

[0007] Preparation of S1, In2O3 / ZnCdS composite materials:

[0008] 20-50 mg of In2O3 obtained by conversion of MIL-68(In) was placed in 20 mL of deionized water and ultrasonically dissolved for 25-35 min, then 0.5-0.7 mmol of zinc acetate and 0.5-0.7 mmol of cadmium acetate were added and stirred evenly to obtain a first solution, and the pH value of the first solution was adjusted to 7, and finally 0.5-2.4 mL of a 0.45-0.55 mol / L Na2S aqueous solution was added, and stirred at room temperature for 17.5-18.5 h to obtain a first product, and then the obtained first product was washed and dried to obtain an In2O3 / ZnCdS composite material;

[0009] Preparation of S2, In2O3 / ZnCdS / Pt composite materials:

[0010] A 2.5-3.5 mg / mL chloroplatinic acid aqueous solution, deionized water and triethanolamine solution are mixed uniformly in a mass ratio of 2-8:45:5 to obtain a second solution, and the In2O3 / ZnCdS composite material obtained in step S1 is ultrasonically dissolved in the second solution at a solid-liquid ratio of 1 mg:52-58 mL, the ultrasonic power is 350-450 W, and the ultrasonic dissolution time is 25-35 min to obtain a third solution;

[0011] The third solution was placed in a reactor and evacuated, then the vacuum pump was turned off and a 250-350W xenon lamp was turned on for 55-65 minutes. The second product was then washed and dried to obtain an In2O3 / ZnCdS / Pt composite material.

[0012] Further, the method for obtaining In2O3 by converting MIL-68(In) is:

[0013] The metal organic framework material MIL-68 (In) is placed in a tube furnace, heated to 495-505°C at a heating rate of 4-6°C / min, then kept warm for reaction for 1.5-2.5h, and then cooled to room temperature to obtain In2O3.

[0014] Description: MIL-68 (In) as a precursor can be completely decomposed and converted into In2O3 at high temperature, retaining the structural characteristics of the precursor. High-temperature heat treatment can effectively remove the organic components in the precursor to obtain In2O3 with higher purity.

[0015] Furthermore, the preparation method of the metal organic framework material MIL-68 (In) is:

[0016] 1.7-1.9 mmol In(NO3)3 and 1.7-1.9 mmol H2BDC were dissolved in 14-16 mL DMF solution, and then 79-81 μL of 0.03-0.05 mol / L crystalline sodium acetate aqueous solution was dropped, and stirred evenly to obtain a fourth solution. The fourth solution was transferred to a 150 ml flask, and reacted in an oil bath at 95-105°C for 25-35 min. After the reaction, it was cooled to room temperature, and the third product was washed and dried to obtain the metal organic framework material MIL-68 (In).

[0017] Description: Using DML as a solvent can dissolve metal salts and organic ligands, providing a good environment for the reaction; by adding sodium acetate aqueous solution, the pH value can be effectively controlled to promote the crystallization and precipitation of MIL-68 (In); the reaction can be completed at a relatively low temperature without the need for high temperature conditions, thus avoiding possible side reactions or structural damage at high temperatures.

[0018] Furthermore, the method for washing and drying the third product is: first filtering and washing with an ethanol solution, and then placing it in a drying oven at 55 to 65° C. for 11.5 to 12.5 hours.

[0019] Note: Ethanol can effectively dissolve and wash away impurities such as unreacted raw materials and by-products remaining during the reaction process, and the dried product is more stable.

[0020] Furthermore, in step S1, the method for washing and drying the first product is: first filtering and washing with deionized water and ethanol solution, and then placing in a drying oven at 55 to 65° C. and drying for 11.5 to 12.5 hours.

[0021] Note: Deionized water can dissolve and wash away inorganic salt impurities with strong polarity, while ethanol can dissolve and wash away organic impurities. The combination of the two solvents can more comprehensively remove various impurities and improve product purity.

[0022] Furthermore, in step S2, the method for washing and drying the second product is: first centrifugally washing with deionized water and ethanol solution, wherein the centrifugal speed is 7500-8500 r / min, the time is 4-6 min, and then placed in a drying oven at 55-65°C for 11.5-12.5 h.

[0023] Description: Centrifugal washing is suitable for separating tiny particles, colloids or sediments, and centrifugal washing can remove impurities more thoroughly and achieve better separation effects.

[0024] Furthermore, in step S2, the vacuuming time is 10 to 15 minutes, and the vacuum degree is -0.15 to -0.05 MPa.

[0025] Note: The higher the degree of vacuuming, the better the bubbles in the solution can be removed, which is beneficial to improving the density and mechanical properties of the composite material; if the degree of vacuuming is not enough, the bubbles remaining in the solution will cause defects and pores inside the composite material; the higher the degree of vacuuming, the faster the solvent evaporates, which is beneficial to shorten the preparation time and improve production efficiency, but if the evaporation is too fast, it may cause cracks on the surface of the material or lose uniformity.

[0026] Further, in step S2, the In2O3 / ZnCdS composite material obtained in step S1 is firstly separated into material A and material B with a mass ratio of 1:3-5, and the material A and material B are surface-treated to obtain the surface-treated material A and the surface-treated material B respectively; the surface-treated material A is then ultrasonically dissolved in the second solution, and the vacuum is evacuated to a vacuum degree of 1-3 MPa, and the surface-treated material B is then added, and the vacuum is evacuated to a vacuum degree of -0.15--0.05 MPa, and the ultrasonic dissolution is continued until the vacuum pump is turned off;

[0027] The surface treatment method of material A is as follows: freeze-thaw material A for 2 to 3 times in a liquid nitrogen environment, with a liquid nitrogen gas flow rate of 30 to 40 L / min and a freezing temperature of -20 to -10°C, and perform femtosecond laser etching on the surface of material A obtained by freeze-thaw to obtain material A after surface treatment;

[0028] The surface treatment method for the B material is as follows: after femtosecond laser etching of the B material, the B material after femtosecond laser etching is immersed in a sodium chloride solution with a solid-liquid ratio of 1 mg: 20-30 mL for sensitization treatment for 5-10 minutes to obtain the surface-treated B material;

[0029] The laser wavelength used in the femtosecond laser etching is 1030nm, the laser spot size is 15-25μm, the laser pulse width is 270-280fs, the single pulse energy is 3.2-3.4μJ, the frequency is 100-300kHz, the scanning speed is 200-450mm / s, the scanning spacing is 20-40μm, and the number of scans is 10-30 times.

[0030] Note: Freezing and thawing the smaller portion with liquid nitrogen can increase the porosity and specific surface area of ​​the material, which is conducive to the production of more active sites during subsequent femtosecond laser etching, while femtosecond laser etching and sensitization treatment of the larger portion can improve the material's light absorption capacity and charge separation efficiency. The two materials are compounded with the second solution after different treatments to synergistically enhance the photoelectric properties of the composite material; first dissolving the smaller portion in the second solution under low vacuum can increase the contact area between the material and the solution, promote uniform distribution and rapid reaction of the reactants, and then adding the larger portion under high vacuum can accelerate solvent evaporation, promote close bonding between materials, and improve reaction efficiency and product purity.

[0031] An application of an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution prepared by any of the methods described above, wherein the In2O3 / ZnCdS / Pt composite material is applied to photocatalytic hydrogen production.

[0032] Furthermore, the method for applying the In2O3 / ZnCdS / Pt composite material to photocatalytic hydrogen production is as follows:

[0033] The In2O3 / ZnCdS / Pt composite material was ultrasonically dissolved in a 10% volume fraction TEOA aqueous solution at a solid-liquid ratio of 1g:2mL at room temperature, and then the TEOA aqueous solution containing the In2O3 / ZnCdS / Pt composite material was irradiated with a 300W xenon lamp for 5h to achieve photocatalytic hydrogen production.

[0034] Description: The In2O3 / ZnCdS / Pt composite material prepared in this application is used for photocatalytic hydrogen production from TEOA aqueous solution, which can effectively absorb the visible light part of sunlight and improve the photocatalytic efficiency.

[0035] Compared with the existing nanocomposite materials for photocatalytic hydrogen evolution, the beneficial effects of the present invention are:

[0036] (1) The preparation of the In2O3 / ZnCdS / Pt composite material of the present invention uses MIL-68 as a precursor. The retention of the rod-like morphology of MIL-68 provides more active sites for the hydrogen evolution reaction and increases the specific surface area of ​​the semiconductor. The hollow tube structure of In2O3 allows multiple reflections of visible light in the hollow cavity, laying the foundation for higher photocatalytic efficiency. In2O3 and Pt as dual co-catalysts improve the surface hydrogen evolution reaction kinetics, promote charge separation and transfer on the semiconductor / co-catalyst and co-catalyst / H2O dual interfaces, and significantly improve the hydrogen production rate. This lays the foundation for the development of semiconductor-based photocatalysts with multi-interface regulation capabilities.

[0037] (2) The preparation of the In2O3 / ZnCdS / Pt composite material of the present invention forms a heterogeneous structure, and the internal electric field is formed between the co-catalyst and the semiconductor, which changes the transmission pathway of electrons and holes, inhibits the recombination of electrons and holes, reduces the photocorrosion of ZnCdS, and more directly and effectively realizes the improvement of photocatalytic hydrogen evolution activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a graph showing the XRD test results of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention;

[0039] Figure 2This is a standard comparison diagram of the SEM test results of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention;

[0040] Figure 3 This is a TEM test result diagram of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention;

[0041] Figure 4 This is a graph showing the XPS test results of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention;

[0042] Figure 5 This is a UV-visible diffuse reflectance spectrum test result diagram of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention;

[0043] Figure 6 This is a graph showing the transient photocurrent test results of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention;

[0044] Figure 7 This is a graph showing the electrochemical impedance test results of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention;

[0045] Figure 8 is a Mott-Schottky curve diagram of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention;

[0046] Fig. 9 This is a test diagram of the photocatalytic hydrogen evolution activity of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention;

[0047] Fig.10 This is a diagram of the photocatalytic reaction mechanism of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0048] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0049] Example 1: A method for preparing an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution, comprising the following steps:

[0050] Preparation of S1, In2O3 / ZnCdS composite materials:

[0051] 40 mg of In2O3 obtained by conversion of MIL-68(In) was placed in 20 mL of deionized water and ultrasonically dissolved for 30 min, followed by adding 0.6 mmol of zinc acetate and 0.6 mmol of cadmium acetate and stirring evenly to obtain a first solution, and the pH value of the first solution was adjusted to 7 with a 0.2 mol / L NaOH solution, and finally 1.5 mL of a 0.5 mol / L Na2S aqueous solution was added, and stirred at room temperature for 18 h to obtain a first product, and then the obtained first product was washed and dried to obtain an In2O3 / ZnCdS composite material;

[0052] The method for washing and drying the first product is: first filtering and washing with deionized water and ethanol solution, and then drying in a drying oven at 60° C. for 12 hours;

[0053] The method for obtaining In2O3 by converting MIL-68(In) is:

[0054] The metal organic framework material MIL-68 (In) is placed in a tube furnace, heated to 500°C at a heating rate of 5°C / min, kept warm for 2 hours, and then cooled to room temperature to obtain In2O3;

[0055] The preparation method of the metal organic framework material MIL-68 (In) is:

[0056] 1.8 mmol of In(NO3)3 and 1.8 mmol of H2BDC were dissolved in 15 mL of DMF solution, and then 80 μL of 0.04 mol / L crystalline sodium acetate aqueous solution was dropped and stirred to obtain a fourth solution. The fourth solution was then transferred to a 150 ml flask and reacted in an oil bath at 100° C. for 30 min. After the reaction was completed, it was cooled to room temperature, and the third product was washed and dried to obtain a metal organic framework material MIL-68 (In);

[0057] The method for washing and drying the third product is: first filtering and washing with an ethanol solution, and then drying in a drying oven at 60° C. for 12 hours;

[0058] Preparation of S2, In2O3 / ZnCdS / Pt composite materials:

[0059] A 3 mg / mL chloroplatinic acid aqueous solution, deionized water and triethanolamine solution were mixed uniformly in a mass ratio of 6:45:5 to obtain a second solution, and the In2O3 / ZnCdS composite material obtained in step S1 was ultrasonically dissolved in the second solution at a solid-liquid ratio of 1 mg:54 mL, the ultrasonic power was 400 W, and the ultrasonic dissolution time was 30 min to obtain a third solution;

[0060] The third solution was placed in a reactor and evacuated for 13 minutes at a vacuum degree of -0.1 MPa. The vacuum pump was turned off and a 300W xenon lamp was turned on for 60 minutes. The second product was then washed and dried. The second product was washed and dried by centrifugation with deionized water and ethanol solution at a speed of 8000 r / min for 5 minutes. The product was then placed in a drying oven at 60°C and dried for 12 hours to obtain an In2O3 / ZnCdS / Pt composite material.

[0061] Example 2: The In2O3 / ZnCdS / Pt composite material prepared in Example 1 is applied to photocatalytic hydrogen production. The method is as follows: the In2O3 / ZnCdS / Pt composite material is ultrasonically dissolved in a 10% by volume TEOA aqueous solution at a solid-liquid ratio of 1 g:2 mL at room temperature, and the TEOA aqueous solution in which the In2O3 / ZnCdS / Pt composite material is dissolved is then irradiated with a 300 W xenon lamp for 5 hours to achieve photocatalytic hydrogen production.

[0062] Example 3: This example is different from Example 1 in that 1.7 mmol of In(NO3)3 and 1.7 mmol of H2BDC are dissolved in 14 mL of DMF solution, and then 81 μL of 0.05 mol / L crystalline sodium acetate aqueous solution is dropped into it and stirred evenly to obtain a fourth solution.

[0063] Example 4: This example is different from Example 1 in that 1.9 mmol of In(NO3)3 and 1.9 mmol of H2BDC are dissolved in 16 mL of DMF solution, and then 79 μL of 0.03 mol / L crystalline sodium acetate aqueous solution is dropped into it and stirred evenly to obtain a fourth solution.

[0064] Example 5: This example is different from Example 1 in that the fourth solution is transferred to a 150 ml flask and reacted in an oil bath at 95° C. for 25 min.

[0065] Example 6: This example is different from Example 1 in that the fourth solution is transferred to a 150 ml flask and reacted in an oil bath at 105° C. for 35 min.

[0066] Example 7: This example is different from Example 1 in that the metal organic framework material MIL-68 (In) is placed in a tube furnace, heated to 495°C at a heating rate of 4°C / min, kept warm for 1.5 hours, and then cooled to room temperature to obtain In2O3.

[0067] Example 8: This example is different from Example 1 in that the metal organic framework material MIL-68 (In) is placed in a tube furnace, heated to 505°C at a heating rate of 6°C / min, kept warm for 2.5 hours, and then cooled to room temperature to obtain In2O3.

[0068] Example 9: This example is different from Example 1 in that 20 mg of In2O3 obtained by conversion of MIL-68(In) is placed in 20 mL of deionized water and ultrasonically dissolved for 25 min, followed by adding 0.7 mmol of zinc acetate and 0.7 mmol of cadmium acetate and stirring evenly to obtain a first solution.

[0069] Example 10: This example is different from Example 1 in that 50 mg of In2O3 obtained by conversion of MIL-68(In) is placed in 20 mL of deionized water and ultrasonically dissolved for 35 min, and then 0.5 mmol of zinc acetate and 0.5 mmol of cadmium acetate are added and stirred evenly to obtain a first solution.

[0070] Example 11: This example is different from Example 1 in that 0.5 mL of 0.45 mol / L Na2S aqueous solution is added and stirred at room temperature for 17.5 h.

[0071] Example 12: This example is different from Example 1 in that 2.4 mL of 0.55 mol / L Na2S aqueous solution is added and stirred at room temperature for 18.5 h.

[0072] Example 13: This example is different from Example 1 in that a 2.5 mg / mL chloroplatinic acid aqueous solution, deionized water and triethanolamine solution are uniformly mixed in a mass ratio of 2:45:5 to obtain a second solution.

[0073] Example 14: This example is different from Example 1 in that a 3.5 mg / mL chloroplatinic acid aqueous solution, deionized water and triethanolamine solution are uniformly mixed in a mass ratio of 8:45:5 to obtain a second solution.

[0074] Example 15: This example is different from Example 1 in that the In2O3 / ZnCdS composite material obtained in step S1 is ultrasonically dissolved in the second solution at a solid-liquid ratio of 1 mg:52 mL, the ultrasonic power is 350 W, and the ultrasonic dissolution time is 25 min to obtain a third solution.

[0075] Example 16: This example is different from Example 1 in that the In2O3 / ZnCdS composite material obtained in step S1 is ultrasonically dissolved in the second solution at a solid-liquid ratio of 1 mg:58 mL, the ultrasonic power is 450 W, and the ultrasonic dissolution time is 35 min to obtain a third solution.

[0076] Example 17: This example is different from Example 1 in that after the third solution is placed in a reactor and evacuated, the evacuation time is 10 minutes, the vacuum degree is -0.15 MPa, the vacuum pump is turned off and a 250W xenon lamp is turned on for 55 minutes.

[0077] Example 18: This example is different from Example 1 in that after the third solution is placed in a reactor and evacuated, the evacuation time is 15 minutes, the vacuum degree is -0.05 MPa, the vacuum pump is turned off and a 350W xenon lamp is turned on for 65 minutes.

[0078] Example 19: The difference between this example and Example 1 is that the method for washing and drying the first product is: first filtering and washing with deionized water and ethanol solution, and then placing it in a drying oven at 55°C for 11.5 hours; the method for washing and drying the second product is: first centrifugally washing with deionized water and ethanol solution, wherein the centrifugal speed is 7500r / min, the time is 4min, and then placing it in a drying oven at 55°C for 11.5 hours; the method for washing and drying the third product is: first filtering and washing with ethanol solution, and then placing it in a drying oven at 55°C for 11.5 hours.

[0079] Example 20: The difference between this example and Example 1 is that the method for washing and drying the first product is: first filtering and washing with deionized water and ethanol solution, and then placing it in a drying oven at 65°C for 12.5 hours; the method for washing and drying the second product is: first centrifugally washing with deionized water and ethanol solution, wherein the centrifugal speed is 8500r / min, the time is 6min, and then placing it in a drying oven at 65°C for 12.5 hours; the method for washing and drying the third product is: first filtering and washing with ethanol solution, and then placing it in a drying oven at 65°C for 12.5 hours.

[0080] Example 21: This example is different from Example 1 in that, in step S2, the In2O3 / ZnCdS composite material obtained in step S1 is first separated into material A and material B in a mass ratio of 1:4, and material A and material B are surface-treated to obtain surface-treated material A and surface-treated material B, respectively; the surface-treated material A is ultrasonically dissolved in the second solution, evacuated to a vacuum degree of 2 MPa, and the surface-treated material B is added, and evacuated to a vacuum degree of -0.1 MPa, and ultrasonic dissolution is continued until the vacuum pump is turned off;

[0081] The surface treatment method of material A is as follows: freeze-thaw material A twice in a liquid nitrogen environment, with a liquid nitrogen gas flow rate of 35 L / min and a freezing temperature of -15°C, and perform femtosecond laser etching on the surface of material A obtained by freeze-thaw to obtain material A after surface treatment;

[0082] The surface treatment method for material B is as follows: after femtosecond laser etching of material B, the material B after femtosecond laser etching is immersed in a sodium chloride solution with a solid-liquid ratio of 1 mg:25 mL for sensitization treatment for 8 minutes to obtain the surface-treated material B;

[0083] The femtosecond laser etching uses a laser wavelength of 1030 nm, a laser spot size of 18-22 μm, a laser pulse width of 275 fs, a single pulse energy of 3.3 μJ, a frequency of 200 kHz, a scanning speed of 325 mm / s, a scanning interval of 30 μm, and 20 scan times.

[0084] Example 22: This example differs from Example 21 in that the In2O3 / ZnCdS composite material obtained in step S1 is first separated into material A and material B in a mass ratio of 1:3.

[0085] Example 23: This example differs from Example 21 in that the In2O3 / ZnCdS composite material obtained in step S1 is first separated into material A and material B in a mass ratio of 1:5.

[0086] Example 24: The difference between this example and Example 21 is that after material A is freeze-thawed twice in a liquid nitrogen environment, the liquid nitrogen gas flow rate is 30 L / min, the freezing temperature is -20°C, and the surface of material A obtained by freeze-thaw is subjected to femtosecond laser etching to obtain surface-treated material A.

[0087] Example 25: The difference between this example and Example 21 is that after material A is freeze-thawed three times in a liquid nitrogen environment, the liquid nitrogen gas flow rate is 40 L / min, the freezing temperature is -10°C, and the surface of material A obtained by freeze-thaw is subjected to femtosecond laser etching to obtain surface-treated material A.

[0088] Example 26: This example differs from Example 21 in that the surface-treated material A is ultrasonically dissolved in the second solution, and the solution is evacuated to a vacuum degree of 1 MPa. The surface-treated material B is then added and evacuated to a vacuum degree of -0.05 MPa. The ultrasonic dissolution is continued until the vacuum pump is turned off.

[0089] Example 27: This example differs from Example 21 in that the surface-treated material A is ultrasonically dissolved in the second solution, and the solution is evacuated to a vacuum degree of 3 MPa. The surface-treated material B is then added and evacuated to a vacuum degree of -0.15 MPa. The ultrasonic dissolution is continued until the vacuum pump is turned off.

[0090] Example 28: The difference between this example and Example 21 is that the laser wavelength used in the femtosecond laser etching is 1030nm, the laser spot size is 15-18μm, the laser pulse width is 270fs, the single pulse energy is 3.2μJ, the frequency is 100kHz, the scanning speed is 200mm / s, the scanning spacing is 20μm, and the number of scans is 10 times.

[0091] Example 29: The difference between this example and Example 21 is that the laser wavelength used in the femtosecond laser etching is 1030nm, the laser spot size is 22-25μm, the laser pulse width is 280fs, the single pulse energy is 3.4μJ, the frequency is 300kHz, the scanning speed is 450mm / s, the scanning spacing is 40μm, and the number of scans is 30 times.

[0092] Example 30: This example is different from Example 21 in that after the B material is subjected to femtosecond laser etching, the femtosecond laser etched B material is immersed in a sodium chloride solution with a solid-liquid ratio of 1 mg:20 mL for sensitization treatment for 5 minutes to obtain the surface-treated B material.

[0093] Example 31: This example is different from Example 21 in that after the B material is subjected to femtosecond laser etching, the femtosecond laser etched B material is immersed in a sodium chloride solution with a solid-liquid ratio of 1 mg:30 mL for sensitization treatment for 10 minutes to obtain the surface-treated B material.

[0094] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.

[0095] 1. Observe the morphological characteristics of In2O3 / ZnCdS / Pt composite materials through XRD test, SEM test, etc.

[0096] 1. XRD test was performed on the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention. Figure 1 As shown:

[0097] The In2O3 obtained by calcining MIL-68 in air has a typical cubic structure, which conforms to the standard PDF card of cubic In2O3 (PDF No.06-0416). The diffraction peaks at 35.47, 30.58, 51.04, and 60.68 correspond to the (400), (222), (440), and (622) crystal planes in the standard PDF card of cubic In2O3. The diffraction peaks of the crystal structure of ZnCdS solid solution are between cubic CdS (JCPDS No.42-1411) and cubic ZnS (JCPDS No.02-0565). The diffraction peaks at 52.09, 26.51, and 43.99 correspond to the (311), (111), and (220) crystal planes in the CdS PDF standard card, and the diffraction peaks at 33.15, 59.18, and 69.58 correspond to the (200), (222), and (400) crystal planes in the ZnS PDF standard card. No obvious Pt signal was detected in the prepared In2O3 / ZnCdS / Pt material. Due to the low loading amount and high dispersion of Pt, we speculate that this may be the reason for the missing Pt characteristic peaks.

[0098] 2. The In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention was subjected to SEM test. Figure 2 As shown:

[0099] like Figure 2 As shown in (a), MIL-68 has a rod-like structure with cracks on the surface. The morphology is uniform and the length is about 7 μm. Figure 2 (b) It can be seen that the In2O3 sintered in air retains the main morphology of MIL-68. In2O3 has a hollow rod structure with no cracks on the surface and a slightly reduced size of about 5μm. Figure 2 (c) It can be seen that the sulfurization reaction causes a large number of ZnCdS particles to grow on the surface of In2O3. Figure 2 (d) It can be seen that after Pt atoms are loaded under the photoreduction reaction, no obvious Pt nanoclusters appear, and the overall morphology is no different from that of In2O3 / ZnCdS. This is due to the small amount of Pt loaded and its uniform distribution.

[0100] 3. The In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention was subjected to TEM test. Figure 3 As shown:

[0101] like Figure 3 (a) and Figure 3 As shown in (b), due to the small magnification size, the TEM image only shows the complete morphology of ZnCdS nanoparticles. Figure 3The three regions A, B, and C in (c) are magnified to obtain HRTEM images, such as Figure 3 (d), (e), (f). According to HRTEM image analysis, the interplanar spacings of 0.255nm and 0.178nm correspond to the (400) and (440) planes of In2O3, respectively. The interplanar spacing of 0.156nm corresponds to the (222) plane of ZnCdS.

[0102] 4. XPS test was performed on the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention. Figure 4 As shown:

[0103] In the XPS spectrum of In 3d, that is Figure 4 In (a), two strong characteristic peaks are clearly observed: 444.4eV and 452eV, which are attributed to In 3d5 / 2 and In 3d3 / 2, respectively, indicating that the In element in the sample is In 3+ The O 1s spectrum is as follows Figure 4 (b) shows that there are peaks with binding energies of 529.8 eV and 531.6 eV. The low energy peak at 529.8 eV is attributed to the lattice oxygen of In2O3, and the high energy peak at 531.6 eV is usually attributed to the chemically adsorbed oxygen on the surface. In the Zn 2p high-resolution XPS spectrum of In2O3 / ZnCdS ( Figure 4 (c)), the binding energies of Zn 2p3 / 2 and Zn 2p1 / 2 are located at 1022.1eV and 1045.2eV, respectively. This indicates that there is Zn in the In2O3 / ZnCdS / Pt composite. 2+ chemical state. Figure 4 (d) is the Cd 3d spectrum of the In2O3 / ZnCdS / Pt composite material, with Cd 3d5 / 2 and Cd3d3 / 2 peaks at binding energies of 405.2eV and 412eV, respectively. This indicates that the chemical state of Cd in In2O3 / ZnCdS / Pt is Cd 2+ The Pt 4f 7 / 2 and Pt 4f 5 / 2 peaks are located at 72.3 and 75.7 eV, respectively ( Figure 4 (e)), indicating that Pt was successfully loaded on In2O3 / ZnCdS / Pt. For high-resolution S2p spectra ( Figure 4 (f)), the two peaks at 161.5 eV and 162.4 eV correspond to S2p3 / 2 and S2p1 / 2, respectively, confirming the existence of S in the In2O3 / ZnCdS / Pt composite. 2- In addition, the peak at 167.5 eV is attributed to the oxidation of S ions to sulfate in the air. Therefore, XPS analysis shows that In, O, Cd, Zn and S elements present In, 3+, O 2- 、Cd 2+ 、Zn 2+ and S 2- chemical state, proving the successful preparation of In2O3 / ZnCdS / Pt composite materials.

[0104] 5. The In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention was tested by UV-visible diffuse reflectance spectroscopy. Figure 5 As shown:

[0105] Depend on Figure 5 (a) It can be seen that MIL-68(In) has a good photoresponse in the wavelength range of 200-340nm due to the charge transfer from the ligand to the metal. The light absorption performance of In2O3 obtained after sintering is good in the ultraviolet light region, but poor in the visible light region, and the light absorption range is <320nm. The absorption edge of ZnCdS is 500nm. With the loading of ZnCdS, the absorption edge of In2O3 / ZnCdS has a red shift, indicating that the visible light response of the material is enhanced. The light absorption range of In2O3 / ZnCdS is <490nm. After photodeposition loading of Pt, the light absorption range did not widen significantly, but the absorption of In2O3 / ZnCdS / Pt composite material in the visible light region of 490-800nm ​​was significantly enhanced. It can be seen that In2O3 / ZnCdS / Pt has strong light absorption characteristics. The addition of In2O3 and Pt forms a heterogeneous interface, which in turn expands the absorption range of the photocatalyst, promotes the formation of photogenerated electrons, and promotes the photocatalytic reaction. Figure 5 (a) Draw Tauc Figure 5 (b), the calculated band gap values ​​of In2O3 and ZnCdS are 2.88eV and 2.5eV respectively.

[0106] 6. The transient photocurrent test of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention is as follows: Figure 6 As shown:

[0107] The current intensity generated by the In2O3 photocurrent is weak and negligible, while the In2O3 / ZnCdS / Pt photocurrent shows a relatively large photocurrent response during the switching cycle of visible light irradiation. Compared with In2O3, the In2O3 / ZnCdS / Pt photocatalyst significantly improves the transfer and separation of carriers.

[0108] 7. Electrochemical impedance spectroscopy was performed on the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention. Figure 7 As shown:

[0109] The arc radius of In2O3 / ZnCdS / Pt is small, the resistance is small, the electron mobility is high, and the separation effect of electrons and holes is good.

[0110] 8. The Mott-Schottky curve test of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention is as follows: Figure 8 As shown:

[0111] The slopes of the curves of In2O3 and ZnCdS are positive, so both In2O3 and ZnCdS are n-type semiconductors. According to the formula, the flat band potential of In2O3 is -0.15eV, and the flat band potential of ZnCdS is -0.95eV. Therefore, it can be determined that the conduction band potential (ECB) of In2O3 and ZnCdS is -0.35eV and -1.15eV respectively relative to NHE.

[0112] 9. The photocatalytic hydrogen evolution activity of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention was tested. Fig. 9 As shown:

[0113] Depend on Fig. 9 (a)(b) It can be seen that In2O3 itself has no hydrogen evolution activity, but In2O3 can be used as a co-catalyst to further improve the hydrogen evolution rate of single ZnCdS. With the increase of the amount of co-catalyst In2O3 added, the photocatalytic hydrogen evolution rate of In2O3 / ZnCdS shows a trend of first increasing and then decreasing. Excessive In2O3 hinders the light absorption of ZnCdS, reduces the generation of photogenerated carriers, and affects the photocatalytic hydrogen evolution rate. When 40 mg In2O3 is added, the hydrogen evolution rate of In2O3 / ZnCdS is the highest, which is 217.9 μmol g -1 h -1 , the hydrogen evolution rate is expanded to 1.5 times that of single ZnCdS.

[0114] Then, In2O3 / ZnCdS with 40 mg of In2O3 as the precursor was used for photoreduction reaction to load Pt. Fig. 9 (c) (d) It can be seen that with the increase of the amount of Pt element added, the photocatalytic hydrogen evolution rate increases first and then decreases. When the amount of Pt element added is 18 mg, the photocatalytic hydrogen evolution rate of In2O3 / ZnCdS / Pt is the highest, which is 7294.7 μmol g -1 h -1. It can be seen that the appropriate addition of Pt greatly improves the hydrogen evolution activity of the photocatalyst, while excessive Pt doping will form Pt clusters and reduce the hydrogen evolution rate. Using the same product 40mgIn2O3 / ZnCdS / Pt as a precursor, the photocatalytic hydrogen evolution rate before and after Pt loading can be expanded by nearly 33.5 times. In this catalyst, the addition of In2O3 and Pt as co-catalysts changes the electron transmission pathway and provides more active sites, further effectively improving the hydrogen evolution activity.

[0115] 10. The photocatalytic hydrogen evolution activity of the In2O3 / ZnCdS / Pt composite material prepared in Example 1 of the present invention was tested. Fig.10 As shown:

[0116] Under light, both In2O3 and ZnCdS can generate electrons and holes. Due to the formation of a heterojunction at the interface, the electrons in the ZnCdS conduction band can quickly move to the In2O3 conduction band, and finally transfer to the photogenerated electrons on the Pt atoms and react with the H + The reaction generates H2. The photogenerated holes are transferred from the valence band of In2O3 to the valence band of ZnCdS, and then captured by the sacrificial agent TEOA. Therefore, the combination of In2O3, ZnCdS and Pt can effectively accelerate the transport of photoexcited electrons and photogenerated holes in space, so that more electrons can participate in the photocatalytic hydrogen production process. In addition, the mesoporous structure provided by the MOF precursor can be used for H2O, H + The reactant molecules such as In2O3 and hole scavengers provide abundant active sites, thereby promoting the reaction kinetics and improving the photocatalytic activity. In conclusion, the In2O3 / ZnCdS / Pt composite material promotes photocatalytic hydrogen evolution through the synergistic effects of enhanced visible light absorption, heterojunction formation, and mesoporous structure.

[0117] 2. Experiments were conducted to demonstrate the hydrogen evolution performance of the In2O3 / ZnCdS / Pt composite material prepared by the present invention.

[0118] 1. In order to illustrate the hydrogen evolution performance of the In2O3 / ZnCdS / Pt composite material prepared by the present invention, In2O3 / ZnCdS / Pt with different In2O3 addition amounts, In2O3 / ZnCdS with different In2O3 addition amounts, In2O3 alone and ZnCdS alone were ultrasonically dissolved in a 10% TEOA aqueous solution at a solid-liquid ratio of 1 g:2 mL to obtain a mixed solution, and the mixed solution was placed in a reactor connected to a photocatalytic activity evaluation system, and then the reactor was evacuated to a vacuum degree of -0.1 MPa, and then the air generator and the cooling water circulation machine were turned on, and the cooling water temperature was set to 5°C, and then the vacuum pump was turned off, the glass tube valve of the photocatalytic activity evaluation system was adjusted, and a 300W xenon lamp was turned on, and the hydrogen evolution amount was tested by gas chromatograph, and the sample was injected every 1 hour, and the hydrogen evolution amount and photocatalytic hydrogen evolution rate of the photocatalyst were calculated according to the peak area detected by the system;

[0119] Design the following experimental groups. The specific comparative data of the following experimental groups are shown in Table 1:

[0120] Blank group 1: The amount of In2O3 added was 20 mg, and the hydrogen evolution activity of In2O3 / ZnCdS was tested.

[0121] Control group 1: The amount of In2O3 added was 30 mg, and the hydrogen evolution activity of In2O3 / ZnCdS was tested.

[0122] Control group 3: The amount of In2O3 added was 50 mg, and the hydrogen evolution activity of In2O3 / ZnCdS was tested.

[0123] Blank group 2: Based on the addition amount of In2O3 of 40mg, 6mgPt was added to test the hydrogen evolution activity of In2O3 / ZnCdS / Pt.

[0124] Control group 4: On the basis of 40 mg of In2O3, 12 mg of Pt was added to test the hydrogen evolution activity of In2O3 / ZnCdS / Pt.

[0125] Control group 5 (ie, Example 1): 18 mg of Pt was added to 40 mg of In2O3 to test the hydrogen evolution activity of In2O3 / ZnCdS / Pt.

[0126] Control group 6: Based on the addition amount of In2O3 of 40mg, 24mgPt was added to test the hydrogen evolution activity of In2O3 / ZnCdS / Pt.

[0127] Blank group 3: hydrogen evolution activity of In2O3 alone.

[0128] Blank group 4: hydrogen evolution activity of ZnCdS alone.

[0129] Table 1 Comparison of hydrogen evolution performance of blank group 1 to blank group 4

[0130]

[0131]

[0132] From the data in Table 1, it can be seen that in the blank group 3, In2O3 itself has no hydrogen evolution activity, but In2O3 can be used as a co-catalyst to further improve the hydrogen evolution rate of single ZnCdS. From the blank group 1 and the control groups 1, 2, and 3, it can be seen that with the increase in the amount of co-catalyst In2O3 added, the photocatalytic hydrogen evolution rate of In2O3 / ZnCdS shows a trend of first increasing and then decreasing. When 40 mg In2O3 is added, the hydrogen evolution rate of In2O3 / ZnCdS is the highest, which is 217.9 μmol g -1 h -1 , the hydrogen evolution rate is expanded to 1.5 times that of single ZnCdS.

[0133] It can be seen from the blank group 2 and the control groups 4, 5, and 6 that with the increase of the amount of Pt element added, the photocatalytic hydrogen evolution rate first increases and then decreases. When the amount of Pt element added is 18 mg, the photocatalytic hydrogen evolution rate of In2O3 / ZnCdS / Pt is the highest, which is 7294.7 μmol g -1 h -1 Using the same product 40mgIn2O3 / ZnCdS as the precursor, the photocatalytic hydrogen evolution rate before and after Pt loading can be expanded by nearly 33.5 times.

[0134] The reasons for the above phenomenon are as follows: in the catalyst, the addition of In2O3 and Pt as co-catalysts in appropriate amounts changes the electron transmission pathway and provides more active sites, further effectively improving the hydrogen evolution activity. However, excessive In2O3 will hinder the light absorption of ZnCdS and reduce the generation of photogenerated carriers. Excessive Pt doping will form Pt clusters, all of which will affect the photocatalytic hydrogen evolution rate.

[0135] 2. Investigate the influence of preparation parameters of In2O3 / ZnCdS composite materials on their hydrogen evolution performance.

[0136] Table 2 Hydrogen production rate of In2O3 / ZnCdS / Pt composite materials in Examples 1, 3 to 12 (μmol g -1 h -1 )

[0137]

[0138] It can be seen from the results in Table 2 that the ratio parameters of the fourth solution are too small or too large, the parameters of the fourth solution due to the reaction are too small or too large, the preparation parameters of In2O3 are too small, and the addition parameters of the Na2S aqueous solution are too small or too large, which will reduce the hydrogen production rate of the In2O3 / ZnCdS / Pt composite material. In Example 8, the preparation temperature and time of In2O3 are too long, and the hydrogen production rate is improved compared with Example 1, but the improvement is small. Therefore, from an economic point of view, the parameter effect of Example 1 is relatively better.

[0139] 3. Investigate the influence of preparation parameters of In2O3 / ZnCdS / Pt composite materials on their hydrogen evolution performance.

[0140] Table 3 Hydrogen production rate of In2O3 / ZnCdS / Pt composite materials in Examples 13 to 20 (μmol g -1 h -1 )

[0141]

[0142] It can be seen from the results in Table 3 that the proportion of Pt in the second solution is too small or too large, the parameters for dissolving the In2O3 / ZnCdS composite material in the second solution are too small or too large, the parameters for vacuuming the third solution and irradiating with xenon lamp light are too small or too large, and the washing and drying parameters of the first product, the second product and the third product are too small will reduce the hydrogen production rate of the In2O3 / ZnCdS / Pt composite material. In Example 20, the washing and drying parameters of the first product, the second product and the third product are larger, and the hydrogen production rate is improved compared with Example 1, but the improvement is small. Therefore, from an economic point of view, the parameter effect of Example 1 is relatively better.

[0143] 4. Investigate the influence of preparation parameters on hydrogen evolution performance of In2O3 / ZnCdS and Pt composite.

[0144] Table 4 Hydrogen production rate (μmol g) of In2O3 / ZnCdS / Pt composite materials in Examples 21-30 and Comparative Examples 1-3 -1 h -1 )

[0145]

[0146] The difference between Control Example 1 and Example 21 is that the surface treatment method of Material A is the same as that of Material B;

[0147] The difference between Control Example 2 and Example 21 is that the surface treatment method of Material B is the same as that of Material A;

[0148] The difference between Comparative Example 3 and Example 21 is that material A and material B are not surface treated;

[0149] It can be seen from the results in Table 4 that in Examples 21 to 30, the In2O3 / ZnCdS composite material was treated separately and then composited with Pt, which significantly improved the hydrogen production rate of the In2O3 / ZnCdS / Pt composite material compared with Example 1;

[0150] Comparative Examples 1 and 2 lack the surface treatment for distinguishing between material A and material B, and Comparative Example 3 lacks the surface treatment for material A and material B, which reduces the improvement of the hydrogen production rate of the In2O3 / ZnCdS / Pt composite material compared to Examples 21 to 30;

[0151] By comparing Examples 21 to 30, it can be seen that too small or too large a proportion of material A, too small or too large parameters of freeze-thaw treatment, too small or too large parameters of dissolution of material A and material B in the second solution, too small or too large parameters of femtosecond laser etching, and too small or too large parameters of sensitization treatment will all reduce the effect of improving the hydrogen production rate of the In2O3 / ZnCdS / Pt composite material. Therefore, in comprehensive comparison, the parameter effect of Example 21 is relatively better.

Claims

1. A method for preparing an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution, characterized in that: The following steps are involved: Preparation of S1, In2O3 / ZnCdS composite materials: 20-50 mg of In2O3 obtained by conversion of MIL-68(In) was placed in 20 mL of deionized water and ultrasonically dissolved for 25-35 min, then 0.5-0.7 mmol of zinc acetate and 0.5-0.7 mmol of cadmium acetate were added and stirred evenly to obtain a first solution, and the pH value of the first solution was adjusted to 7, and finally 0.5-2.4 mL of a 0.45-0.55 mol / L Na2S aqueous solution was added, and stirred at room temperature for 17.5-18.5 h to obtain a first product, and then the obtained first product was washed and dried to obtain an In2O3 / ZnCdS composite material; Preparation of S2, In2O3 / ZnCdS / Pt composite materials: A 2.5-3.5 mg / mL chloroplatinic acid aqueous solution, deionized water and triethanolamine solution are mixed uniformly in a mass ratio of 2-8:45:5 to obtain a second solution, and the In2O3 / ZnCdS composite material obtained in step S1 is ultrasonically dissolved in the second solution at a solid-liquid ratio of 1 mg:52-58 mL, the ultrasonic power is 350-450 W, and the ultrasonic dissolution time is 25-35 min to obtain a third solution; The third solution was placed in a reactor and evacuated, then the vacuum pump was turned off and a 250-350W xenon lamp was turned on for 55-65 minutes. The second product was then washed and dried to obtain an In2O3 / ZnCdS / Pt composite material.

2. The method for preparing an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution according to claim 1, characterized in that: The method for obtaining In2O3 by converting MIL-68(In) is: The metal organic framework material MIL-68 (In) is placed in a tube furnace, heated to 495-505°C at a heating rate of 4-6°C / min, then kept warm for reaction for 1.5-2.5h, and then cooled to room temperature to obtain In2O3.

3. The method for preparing an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution according to claim 2, characterized in that: The preparation method of the metal organic framework material MIL-68 (In) is: 1.7-1.9 mmol In(NO3)3 and 1.7-1.9 mmol H2BDC were dissolved in 14-16 mL DMF solution, and then 79-81 μL of 0.03-0.05 mol / L crystalline sodium acetate aqueous solution was dropped, and stirred evenly to obtain a fourth solution. The fourth solution was transferred to a 150 ml flask, and reacted in an oil bath at 95-105°C for 25-35 min. After the reaction, it was cooled to room temperature, and the third product was washed and dried to obtain the metal organic framework material MIL-68 (In).

4. The method for preparing an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution according to claim 3, characterized in that: The method for washing and drying the third product is: first filtering and washing with an ethanol solution, and then placing it in a drying oven at 55 to 65° C. and drying it for 11.5 to 12.5 hours.

5. The method for preparing an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution according to claim 1, characterized in that: In step S1, the method for washing and drying the first product is: first filtering and washing with deionized water and ethanol solution, and then placing in a drying oven at 55-65° C. to dry for 11.5-12.5 hours.

6. The method for preparing an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution according to claim 1, characterized in that: In step S2, the method for washing and drying the second product is: first centrifugally washing with deionized water and ethanol solution, wherein the centrifugal speed is 7500-8500 r / min, the time is 4-6 min, and then placed in a drying oven at 55-65°C for 11.5-12.5 h.

7. The method for preparing an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution according to claim 1, characterized in that: In step S2, the vacuuming time is 10 to 15 minutes, and the vacuum degree is -0.15 to -0.05 MPa.

8. The method for preparing an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution according to claim 1, characterized in that: In step S2, the In2O3 / ZnCdS composite material obtained in step S1 is firstly divided into material A and material B with a mass ratio of 1:3-5, and the material A and the material B are surface-treated to obtain the surface-treated material A and the surface-treated material B respectively; Then, the surface treated material A is ultrasonically dissolved in the second solution, and the vacuum is evacuated to a vacuum degree of 1 to 3 MPa. Then, the surface treated material B is added, and the vacuum is evacuated to a vacuum degree of -0.15 to -0.05 MPa. The ultrasonic dissolution is continued until the vacuum pump is turned off. The surface treatment method of material A is as follows: freeze-thaw material A for 2 to 3 times in a liquid nitrogen environment, with a liquid nitrogen gas flow rate of 30 to 40 L / min and a freezing temperature of -20 to -10°C, and perform femtosecond laser etching on the surface of material A obtained by freeze-thaw to obtain material A after surface treatment; The surface treatment method for the B material is as follows: after femtosecond laser etching of the B material, the B material after femtosecond laser etching is immersed in a sodium chloride solution with a solid-liquid ratio of 1 mg: 20-30 mL for sensitization treatment for 5-10 minutes to obtain the surface-treated B material; The laser wavelength used in the femtosecond laser etching is 1030nm, the laser spot size is 15-25μm, the laser pulse width is 270-280fs, the single pulse energy is 3.2-3.4μJ, the frequency is 100-300kHz, the scanning speed is 200-450mm / s, the scanning spacing is 20-40μm, and the number of scans is 10-30 times.

9. Use of an In2O3 / ZnCdS / Pt composite material for photocatalytic hydrogen evolution prepared by the method according to any one of claims 1 to 8, characterized in that: The In2O3 / ZnCdS / Pt composite material is applied to photocatalytic hydrogen production.

10. The use according to claim 9, characterized in that The method for applying the In2O3 / ZnCdS / Pt composite material to photocatalytic hydrogen production is as follows: The In2O3 / ZnCdS / Pt composite material was ultrasonically dissolved in a 10% volume fraction TEOA aqueous solution at a solid-liquid ratio of 1g:2mL at room temperature, and then the TEOA aqueous solution containing the In2O3 / ZnCdS / Pt composite material was irradiated with a 300W xenon lamp for 5h to achieve photocatalytic hydrogen production.

Citation Information

Patent Citations

  • Preparation method and application of ZnCdS / NiO composite photocatalyst

    CN116713009A